Is Familism a Motivator or Stressor? Relationships Between Confucian Familism, Emotional Labor, Work-Family Conflict, and Emotional Exhaustion Among Chinese Teachers - Zhu, Xiaoshuang; Tian, Guoxiu; Yin, Hongbiao; He, Wenjie (Frontiers in Psychology, 2021)
To reveal the cultural effect in the job demands-resources model, this study examined how Confucian familism, emotional labor, and work-family conflict explain the variance in teachers’ emotional exhaustion, with a focus on the mediating roles of emotional labor and work-family conflict. With a sample of 3312 teachers in China, the results of this study revealed that surface acting and expression of naturally felt emotion, and work-family conflict mediated the relationship between familism and emotional exhaustion. Moreover, familism positively predicted deep acting, expression of naturally felt emotion, work-family conflict, and emotional exhaustion, while negatively predicted surface acting. These findings suggest that Confucian familism may play the dual role of motivator and stressor for Chinese teachers’ emotional labor and well-being. This study contributes to the job demands-resources theory by revealing the important role of cultural traditions and provides valuable information for interventions to sustain teacher well-being.